2015
DOI: 10.1007/s12020-015-0591-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone therapeutic supplementation on hematopoietic stem/progenitor cells in children with growth hormone deficiency: focus on proliferation and differentiation capabilities

Abstract: We investigated the direct effects of growth hormone (GH) replacement therapy (GH-RT) on hematopoiesis in children with GH deficiency (GHD) with the special emphasis on proliferation and cell cycle regulation. Peripheral blood (PB) was collected from sixty control individuals and forty GHD children before GH-RT and in 3rd and 6th month of GH-RT to measure hematological parameters and isolate CD34+-enriched hematopoietic progenitor cells (HPCs). Selected parameters of PB were analyzed by hematological analyzer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
0
19
1
Order By: Relevance
“…GHT has proven to have a marked effect on erythroid progenitor precursors, but negligible effects on peripheral blood cells. Indeed, a significant impact of GH on hematopoietic progenitor cells was documented in 40 GHD children after 3 and 6 months of GHT [22]. Similarly, Kotzmann et al showed that 11 adult patients had hematopoietic precursor cells in the lower normal range.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…GHT has proven to have a marked effect on erythroid progenitor precursors, but negligible effects on peripheral blood cells. Indeed, a significant impact of GH on hematopoietic progenitor cells was documented in 40 GHD children after 3 and 6 months of GHT [22]. Similarly, Kotzmann et al showed that 11 adult patients had hematopoietic precursor cells in the lower normal range.…”
Section: Discussionmentioning
confidence: 93%
“…Discordant data also come from studies on the effect of GHT on hematopoiesis and few large-scale studies or ones with a long follow-up have been reported in children. The effect of GHT on hematopoietic progenitor cells [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], as well as on erythropoiesis indices in both adults [21,23] and children affected by GHD [2,20,24,25] has been documented. However, some studies document a significant impact of GHT on erythropoiesis indices exclusively in patients with anemia and not in the totality of patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies reported normocytic anemia in untreated GHD adults [8,10] and children [7,[9][10][11], while others reported low hematopoietic precursor cells but not anemia in GHD [14]. However, most authors reported a beneficial effect of GH replacement therapy on red cells with an increase of Hb levels [7-11, 13, 17], red cells mass [12,13], and hematopoietic precursors number [14].…”
Section: Discussionmentioning
confidence: 99%
“…Human studies revealed that GHD in both adults and children can be associated with an impairment of erythropoiesis leading to normocytic anemia [7][8][9][10][11], reduced red cell mass [12,13], or reduced erythroid precursor cells number [14], which improved after GH treatment [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation